Frequency Of Thyroidal Dysfunction In Chronic Hepatitis C Sero Positives - Muhammad Imran; Karim Kammeruddin; Nida Sajid (ziauddin University, 2024)
Background: Hepatitis C virus is proving to be a global disease causing serious and debilitating effects on the general health of the public. It has been recognized that hepatitis C manifests itself through hepatic and a variety of extra hepatic diseases. The common two being; diabetes mellitus and thyroidal dysfunctions. A range of thyroid hormones disturbances are reported in association with hepatitis C infectivity, for example,Overt and Subclinical hyperthyroidism along with Overt and Subclinical hypothyroidism. To determine the relation between Hepatitis C Sero-Positivity and Thyroidal Dysfunction. Methods: We studied 274 Chronic Hep C sero positive, non cirrhotic cases (Jan 2010 -Jun 2014) in OPD of an urban tertiary care hospital (i.e Baqai Medical University Hospital Nazimabad).Out of this, 203(b/w 20 to 60years of age) cases were found to be evaluable (i.e undergone TSH/FT4 evaluation at baseline). TSH, was taken according to age groups (i.e age 20y-54y (0.4-4.2) μIU/ml & 55-87(0.5-8.9) μIU/ml) & FT4 (all age group)0.8-2.7ng/dL. Results: Thyroid dysfunction was found in 17 patients (8.4% [n = 203]).The Thyroidal dysfunction among the study group include; 01 patient with Overt Thyrotoxicosis (5.88% [n = 17]) , 05 with Clinically Hypothyroid (29.41% [n = 17]) status and 11 cases with Sub-Clinical Hypothyroidism (64.70% [n = 17]). Conclusion: An association of thyroidal dysfunction and Chronic HCV infection is noted in the study population without known pre-existing thyroidal disease. Key Words: Hepatitis C, Thyroid dysfunction (TD), Frequency.